Securing agent 111, and the job of software architect. - Arquilla, John; Bugayenko, Yegor (Communications of the ACM, 2018)
The Communications Web site, http://cacm.acm.org, features more than a dozen bloggers in the BLOG@CACM community. In each issue of Communications, we'll publish selected posts or excerpts.twitterFollow us on Twitter at http://twitter.com/blogCACMhttp://cacm.acm.org/blogs/blog-cacmJohn Arquilla describes the new state of cyberspying, while Yegor Bugayenko considers the importance of a software architect to development projects.